Comparison of Sine and Space Vector Modulated Embedded Z-source Inverter fed Three Phase Induction Motor Drive System - R. Malathi; M. Rathinakumar (International Journal of Power Electronics and Drive Systems (IJPEDS), 2016)
This paper deals with performance of photovoltaic powered Embedded Z-Source Inverter (EZSI) fed Induction motor drive. The DC output from the PV-Panel is boosted and converted into AC using Embedded Z-Source Inverter. EZSI system based on the concept of Z-Source Inverter (ZSI), which provides single stage power conversion. The EZSI also produce same voltage gain as that of the ZSI based system. In EZSI the DC source is embedded within the X-shaped LC impedance network, due to this EZSI has the added advantage of inherent source filtering capability , this can be achieved without any extra passive filter. EZSI can produce the AC output voltage which is greater than the DC link voltage. EZSI system also provides ride-through capability under voltage sags. In this paper the performance of space vector modulated EZSI fed Induction Motor Drive is compared with sinusoidal PWM controlled EZSI fed Drive system. The PV powered EZSI fed three phase Induction Motor System is designed, modeled and simulated using MAT LAB-SIMULINK and the corresponding results are presented. This drive system has advantages like voltage boosting ability and reduced harmonic content.